A CLASSICAL REVIEW ON ARSHA (HAEMORRHOIDS/PILES): CURRENT TREATMENT STRATEGIES AND FUTURE PROSPECTS - Kumar, *Ajai; Ajay Kumar, Gupta (International Journal of Ayurveda and Pharma Research, 2016)
Arsha (Piles) is an extremely common problem and it has been reported since thousands of years and its prevalence rate is highest among all anorectal disorders. Piles are unique to human beings. Nearly half of the population generally experience one haemorrhoidal episode at some point during their lives. Arsha (Haemorrhoids) is clinically an engorged condition of haemorrhoidal venous plexus along with abnormally displaced enlarged anal cushion, characterized by inflammed or prolapsed pile mass, bleeding per rectum and some discharge from anus. The term haemorrhoids is popularly used to refer for pathological varicosity of the haemorrhoidal veins due to increased pressure, is usually resulted by straining during defecation, chronic constipation or diarrhoea, pregnancy etc. In modern medical science, many procedures are described for management of haemorrhoids, of which haemorrhoidectomy is commonly preferred by surgeons, but after sometime of excision there is great possibility of reappearance of the disease. But in Ayurveda fourfold management of Arsha has been indicated viz. Bheshaj, Kshar Karma, Agnikarma and Shastra Karma according to chronicity and presentation of the disease. Among these, Bheshaj Chikitsa and Kshar Karmas show wonderful results in management of Arsha. In this review article an attempt has been made to review the studies carried out on Arsha in the department of Shalya Tantra Rishikul Campus, Uttarakhand Ayurved University Haridwar, Uttarakhand.